2012
DOI: 10.1371/journal.pone.0029679
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Surveillance Data to Detect HIV-Infected Persons with Sustained High Viral Load and Durable Virologic Suppression in New York City

Abstract: BackgroundMonitoring of the uptake and efficacy of ART in a population often relies on cross-sectional data, providing limited information that could be used to design specific targeted intervention programs. Using repeated measures of viral load (VL) surveillance data, we aimed to estimate and characterize the proportion of persons living with HIV/AIDS (PLWHA) in New York City (NYC) with sustained high VL (SHVL) and durably suppressed VL (DSVL).Methods/Principal FindingsRetrospective cohort study of all perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
(40 reference statements)
5
34
0
Order By: Relevance
“…We found that the proportion of undetectable viral load varies by individual and neighbourhood-level characteristics wherein socioeconomically disadvantaged areas have the lowest proportions of persons with undetectable viral load and higher CVL, results consistent with previous findings that uptake and/or adherence may be lower in poorer neighbourhoods [20]. Although mean viral load as a measure of CVL is sensitive to the number of viral load laboratory tests reported and to extreme values, differences found between groups were generally small.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the proportion of undetectable viral load varies by individual and neighbourhood-level characteristics wherein socioeconomically disadvantaged areas have the lowest proportions of persons with undetectable viral load and higher CVL, results consistent with previous findings that uptake and/or adherence may be lower in poorer neighbourhoods [20]. Although mean viral load as a measure of CVL is sensitive to the number of viral load laboratory tests reported and to extreme values, differences found between groups were generally small.…”
Section: Discussionsupporting
confidence: 89%
“…Also, our analysis is limited to those who are reported to the HSR and in care. Because HIV-infected populations are dynamic and tend to move more often than HIV-uninfected populations, identifying all HIV-infected New Yorkers is difficult [20]. The limitation that 36% were missing a viral load report in 2008 likely influences observed CVL estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8–12 This single VL measure, however, does not allow a close examination of VL dynamics over time. 4,13,14 Several studies have begun to evaluate longitudinal VL measures. 4,1315 Data from six HIV clinics showed that using a single VL measure to estimate the percentage of HIV patients with durable viral suppression (all VLs < 200 copies m/L) overestimated by 16% (relative difference) over a 12-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with persistently and intermittently high VLs are at higher risk for developing resistant virus (Lucas et al, 1999) and transmitting virus. (Terzian et al, 2012) In this analysis, unsustained virologic control was associated with structural factors including insurance, and unstable housing. These data thus can inform public health decisions regarding strategies to reduce the costs associated with HIV care and reduce HIV associated morbidities.…”
Section: Discussionmentioning
confidence: 70%